2016
DOI: 10.1590/1678-457x.0043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial activity of pecan nut [Carya illinoinensis (Wangenh) C. Koch] shell aqueous extract on minimally processed lettuce leaves

Abstract: Pecan nutshell is a residue from food industry that has potential to be used as biopreservative in foods. The objective of this study was to evaluate the antimicrobial activity of pecan nutshell aqueous extract in vitro and its effectiveness to inhibit spoilage microorganisms on lettuce leaves. The results indicate that the aqueous extract presents inhibitory activity against important foodborne pathogenic bacteria such as Listeria monocytogenes, Salmonella Enteritidis, Staphylococcus aureus, Bacillus cereus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
2
17
0
9
Order By: Relevance
“…Ethnobotanical uses of pecan by-products include the consumption of infusions made from the leaves or nutshells for the treatment and prevention of diabetes, obesity, hypertension, hypercholesterolemia, cancer, tuberculosis, and other oxidative stress-related diseases (Caxambú et al, 2016;Gad et al, 2007;Hilbig et al, 2018;Trevisan et al, 2014). Several studies have been carried out using pecan by-products, mainly as antimicrobial, antidiabetic and cell protective ( Table 7).…”
Section: Biological Activity Of Pecan By-productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnobotanical uses of pecan by-products include the consumption of infusions made from the leaves or nutshells for the treatment and prevention of diabetes, obesity, hypertension, hypercholesterolemia, cancer, tuberculosis, and other oxidative stress-related diseases (Caxambú et al, 2016;Gad et al, 2007;Hilbig et al, 2018;Trevisan et al, 2014). Several studies have been carried out using pecan by-products, mainly as antimicrobial, antidiabetic and cell protective ( Table 7).…”
Section: Biological Activity Of Pecan By-productsmentioning
confidence: 99%
“…Authors attributed this high antifungal activity to the high concentration of hydrolysable and condensed tannins. Caxambú et al (2016) evaluated the effectiveness of a water pecan nutshell extract against Gram+ and Gram-bacteria, and food pathogens. No inhibition was observed for E. coli or fungi.…”
Section: Biological Activity Of Pecan By-productsmentioning
confidence: 99%
“…Several methods are available for extraction of phenolic compounds from plants, including solvent extraction, ultrasound-assisted extraction, microwave-assisted extraction, and supercritical fluid extraction (Glisic et al, 2011;Hossain et al, 2012;Caxambu et al, 2016). Of these methods, ultrasound-assisted extraction (UAE) technology has gained increasing popularity due to its advantageous properties, including high extraction efficiency, good reproducibility, low solvent consumption, speed, low cost, environmental friendliness and easy scale up for industrial applications (Tao et al, 2014;Cravotto et al, 2008;Vinatoru, 2001;Vuong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were observed previously by Sant'Anna et al [22] when spent coffee ground was evaluated. The disability of sugarcane extract to show antimicrobial activity in the present work may be related to a reduced concentration of compounds with antibacterial activity due to the extraction methodology, although Caxambú et al [14], using the same methodology found antibacterial capacity of aqueous extract from pecan nutshell. Also, different phenolic compounds may have different susceptibility to be extracted to the liquid system [9], and, in the present work, possibly not present in the extract to act as an antimicrobial agent.…”
Section: Resultsmentioning
confidence: 66%
“…The extraction of antimicrobial substances was performed by maintaining 10 g of dried sugarcane bagasse with 1 L of boiling distilled water for 10 min under constant stirring (model 754A, Fisatom, Brazil), and then filtered through Whatman filter paper nº1 and immediately used [ 14]. Suspensions of 10 7 CFU/mL of Staphylococcus aureus ATCC25923, Listeria monocytogenes ATCC7644, Listeria innocua, Salmonella Enteritidis ATCC13076 and Escherichia coli ATCC25922 were spread onto Plate Count Agar (PCA) with a sterile swab and aliquots of 0,02 mL of the extract were applied.…”
Section: Antibacterial Activitymentioning
confidence: 99%